Validasi Kuesioner Elemen PBL yang Mempengaruhi Keputusan Belajar Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan - Galuh Suryandari; Yayi Suryo Prabandari; Rossi Sanusi (Jurnal Pendidikan Kedokteran Indonesia, 2015)
Background: Several elements of PBL have been identified and prepared with a questionnaire to be reused. Variables of PBL elements that influence students' learning decisions are assessed using a questionnaire of PBL elements that affect students’ learning decisions. This study is one part of a study reported in a different journal of medical education. The objective of this study was to validate a questionnaire of PBL elements that influence learning decisions of students in FKIK UMY